2013
DOI: 10.5405/jmbe.993
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study develops a non-contact vibro-acoustic detection technique for measuring the defect quantity and determining the imperfection orientation surrounding a bone-implant interface. Acoustic excitation through a miniature loud speaker and vibration response measurement using a capacity-type displacement sensor are applied to accomplish this task to prevent the mass loading effect on the structure to be examined. The proposed non-contact excitationresponse measurements are verified using a series of designa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Compared with invasive methods like removal torque analysis, noninvasive ways are considered more practical in clinics; for instance, the techniques through radiographic observation [1,3], static inspection [4], and dynamic detection [5][6][7] were proposed before. Recently, the resonant frequency analysis and associate device belonging to dynamic detection [5,7,8] have been extensively applied in dental osseointegration assessment, and also considered as a useful clinical tool due to its potentially noncontact detection nature.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with invasive methods like removal torque analysis, noninvasive ways are considered more practical in clinics; for instance, the techniques through radiographic observation [1,3], static inspection [4], and dynamic detection [5][6][7] were proposed before. Recently, the resonant frequency analysis and associate device belonging to dynamic detection [5,7,8] have been extensively applied in dental osseointegration assessment, and also considered as a useful clinical tool due to its potentially noncontact detection nature.…”
Section: Introductionmentioning
confidence: 99%
“…If the primary stability is not high enough, the extra implant mobility may cause bone defects and result in implantation failed eventually. In the former studies, varied techniques, especially resonance frequency analysis (RFA), were developed for quantifying dental implant stability including experimental and numerical ways [2][3][4]. In terms of numerical characterization, Wang et al [2] determined the identifiable stiffness range of interfacial tissue of dental implants by using RFA.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison demonstrated a satisfactory agreement between the simulation of developed bone remodeling and clinical data. Zhuang et al [4] conducted finite element (FE) modal analysis to validate the measured RF through a noncontact vibro-acoustic detection technique. A comparison of bone block model experiments with numerical simulation showed that the RFs in the defect side are significantly smaller than those in the complete one, as well as the value decreasing with the increase of defect amount.…”
Section: Introductionmentioning
confidence: 99%